Anaemia and its associated risk factors among pregnant women in the Gambia. (2024)
Background: Anaemia is a global health problem affecting about a third of the world’s population. In pregnancy, it is a public health concern with consequences for mothers and infants, including maternal death and infant mortality. In low-income countries, 25% indirect maternal mortality and 30% neonatal deaths are due to anaemia in pregnancy. This study aimed to determine the prevalence of anaemia among pregnant women in The Gambia and identify common risk or predisposing factors associated with anaemia in pregnancy among them. Methods: This was a cross-sectional study of 180 consenting pregnant women, who attended two secondary-care level hospital for antenatal care between March and May 2023. They were selected by using a simple random sampling technique. Data were collected using a validated structured questionnaire and participants’ current antenatal cards while SPSS software version 26.0 was used for analyzing data. Results: The findings of this study shows that 21.7% and 8.3% of the pregnant women were anaemic at booking using 11.0g/dl and 10.0g/dl as cut off respectively with the mean haemoglobin concentration of 11.76+-1.36g/dl. The study revealed that anaemia during pregnancy is associated with factors such as educational level (p=0.048) and the average income per month (p=0.039). Majority of the women, (166, 92.2%), have taken malaria prophylaxis but only 95 (52.8%) admitted to sleeping under insecticide-treated mosquito nets which shows the low prevalence of Malaria among the participants (5.6%) Conclusion: The prevalence of anaemia among pregnant women in the Gambia is 21.7% which implies that anaemia is still a public health problem. Therefore, it is important for actions like early booking and improvement on health and nutritional education to be taken in order to reduce anaemia among pregnant women.